„Niech zwierzęta mają prawa!” Monitoring ścigania oraz karania sprawców przestępstw przeciwko zwierzętom - Karaś, Dawid (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article presents results of monitoring the district prosecutors offices and common courts in 2012–2014 in terms of prosecution and punishment of crimes specified in Animal Protection Act. Study was conducted in 2015 by EKOSTRAŻ and Czarna Owca Pana Kota Foundation as a part of the project “Let animals have rights”, realised within the programme Citizens for Democracy and funded by EOG Funds. In this text author describes some sources of problems connected with prosecution and punishment of crimes against animals and suggests how to solve them. In particular, argues in favor of simplification and modification of statutory criteria of the animal abuse crime in order to expand penalization cases of inhumane treatment of animals.
Keywords: przestępstwa przeciwko zwierzętom; oskarżenie; kara; nieludzkie traktowanie zwierząt